Public’s Attribution vs Punitive Behavior in Indonesian Public Relations Practice - Kriyantono, Rachmat; Safitri, Rizky Ika; Riani, Yuyun Agus (Jurnal ILMU KOMUNIKASI, 2017)
The research aims to test situational crisis communication and attribution theories in Indonesian context. Crisis threats companies’ reputation and affects the public’s attribution which will lead to the creation of punitive behavior from the public towards the organization. The study used a quantitative approach with experimental method and content analysis in the pre-research. Involving 90 respondents, the research fi nds that mass media infl uences public’s attribution within the experimental group who were given positive and negative news. The research shows that the crisis history and the relational reputation determine the public attribution toward the initial crisis responsibility.